1992
DOI: 10.1203/00006450-199211000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein Synthesis in Newborn Piglet Intestinal Explants

Abstract: ABSTRACT. To determine the effects of hormones andApo A-I is the major apolipoprotein of plasma HDL and is epidermal growth factor (EGF) on the small intestinal produced by both liver and intestine in the human, rat, and synthesis of apolipoproteins B-48, A-I, and A-IV in the swine (1, 7-10). Its major metabolic role is that of a cofactor for neonatal mammal, apolipoprotein synthesis by proximal lecithin:cholesterol acyltransferase, the enzyme responsible for jejunal explants from 2-d-old female piglets was st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…This observation was also confirmed in vivo by Doi et al (7). It has been recently demonstrated that intestinal apo A-IV synthesis and secretion are upregulated by insulin in both rodents and humans (3,5). Energy homeostasis in the body is accomplished by a highly integrated and redundant neurohumoral system that prevents the effect of short-term fluctuations in energy balance on fat mass (34).…”
Section: Does Apo A-iv Play a Role In The Regulation Of Food Intake Amentioning
confidence: 73%
“…This observation was also confirmed in vivo by Doi et al (7). It has been recently demonstrated that intestinal apo A-IV synthesis and secretion are upregulated by insulin in both rodents and humans (3,5). Energy homeostasis in the body is accomplished by a highly integrated and redundant neurohumoral system that prevents the effect of short-term fluctuations in energy balance on fat mass (34).…”
Section: Does Apo A-iv Play a Role In The Regulation Of Food Intake Amentioning
confidence: 73%
“…Black and Ellinas [24] have also investigated the effects of insulin on apo B synthesis in jejunal explants from newborn piglets. No influence of insulin was recorded in these experiments, suggesting that the modulation of apo B synthesis by insulin may depend on both the stage of development and the species studied.…”
Section: Resultsmentioning
confidence: 99%
“…ApoA-IV synthesis and secretion by the gastrointestinal tract are upregulated by insulin (25)(26)(27). ApoA-IV enhances basolateral TG secretion in a association between apoB48 concentrations and body mass index (BMI).…”
Section: Association Between Jejunal Lipid Content and Other Variablesmentioning
confidence: 99%